Canada’s Refugee Strategy – How It Can Be Improved - Robert Vineberg (The School of Public Policy Publications, 2018)
When citizens lose faith in their government’s refugee policies, there arises the potential for an anti-immigration backlash, as several European countries have recently discovered. Canada has yet to see that happen, but it has for too long been muddling along with a refugee-processing system that is seriously flawed. Refugees go unprocessed for years, and in the meantime end up living, working and laying down roots. Often that only increases the chances they will end up staying even if they might have otherwise been rejected. It may even lead to increases in questionable refugee claims, as people realize they can work and make money in Canada for years before their case is even heard.